Enhancement of vitamin D2 stability in fortified milk during light exposure and commercial heat treatments by complexation with milk proteins. (June 2019) - Syama, M.A.; Arora, Sumit; Gupta, Chitra; Sharma, Apurva; Sharma, Vivek
Abstract: In India, changes in the life style pattern together with low consumption of vitamin D rich foods resulted in 50–90% of population as vitamin D deficient. Fortification is the common practice followed to overcome such micronutrient deficiencies. Vitamin D is fat soluble in nature and simultaneously sensitive to light and heat, however binding to milk protein improves the solubility and stability towards heat and light. Sodium caseinate, succinylated sodium caseinate (SNaCas), reassembled sodium caseinate (RNaCas) and reassembled succinylated sodium caseinate (RSNaCas) were complexed with ergocalciferol (vitamin D2 ). Milk protein-vitamin D2 complexes (NaCas-VD, SNaCas-VD, RNaCas-VD and RSNaCas-VD) and free vitamin D2 (free-VD) showed highest stability when stored at −20 °C, followed by 4 °C and 37 °C. At the end of storage period of 48 h, the stability (%) of vitamin D2 in milk protein-vitamin D2 complex and free vitamin D2 (free-VD) fortified milk was significantly higher (p < 0.05) in fortified samples stored in transparent glass bottles (upto 53.88%) as compared to samples stored in low density polyethylene (LDPE) pouches (upto 49.56%) upon exposure to different light intensities (1485, 2970, 4455 lux). Complexation of vitamin D2 with milk protein provided greater stability to withstand the heat treatments (pasteurization, boiling and sterilization). Stability of vitamin D was greater from milk protein-vitamin D2 fortified milk stored in transparent glass bottles than the fortified milk stored in LDPE pouches. Highlights: Complexes showed the highest stability at −20 °C and lowest stability at 37 °C. Glass bottles are more effective packaging material as compared to LDPE pouches. Complexation of vitamin D2 to milk protein improves its stability. Free vitamin D (fat soluble) showed the lowest vitamin D stability.